Berdialog dengan Al-Qur’an: Perspektif Rasional-Filosofis - Gozali, Aktobi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2009)
This article deals with the way of repositioning of al-Qur’an dealing with the subject in order to understand the meaning of al-Qur’an to be more contextual and applied in response to various issues of life. A rational-philosophical approach to the delivery of contextual understanding, a necessity when the approach of textual / literal can not provide a good solution at the level of satisfaction ratio, and the practical demands. A repositioning effort that has implications for the conseguences of ontological, epistemological and axiological.